Yap (Y alu polymorphism) signature in six Malay sub-ethnic groups in Peninsular Malaysia / Muhd Shah Jehan Abd Razak - Abd Razak, Muhd Shah Jehan (2015)
Malay sub-ethnic groups in Peninsular Malaysia have a rich culture and tradition such as historical knowledge and heritage, which might be reflected in the current genetic makeup of this population. They are a mixture of different races that were caused by the history of migration centuries ago and consisted of 14 Malay sub-ethnic groups in Peninsular Malaysia. The objective of this study was to analyze the genetic polymorphism of Y chromosome at DYS287 Y Alu Polymorphism (YAP) locus in six Malay sub-ethnic groups of Peninsular Malaysia. A total of 231 buccal cells from healthy unrelated individual males consisting of 117 Kelantan-Malay, 50 Jawa-Malay, 48 Minangkabau-Malay, 9 Banjar Malay, 3 Bugis-Malay and 4 Rao-Malay from different regions of Peninsular Malaysia were screened for the DYS287 Y Alu locus from their genomic DNA. It shows that Kelantan-Malay, Jawa-Malay, Minangkabau-Malay, Banjar-Malay, Bugis-Malay and Rao-Malayare completely absent of theDYS287 Y Alu Polymorphism. Sequence results revealed that all Malay sub-ethnic of Peninsular Malaysia groups studied do not carry the number of 45bp (long) and 28bp (short) with association of long adenine (A)residues at [poly(A) tail] of theAlu sequence at DYS287 locus. Allele frequency for YAP+ was absent in all Malay sub-ethnic groups in Peninsular Malaysia. They were no genetic differences between the studied Malay subethnic groups of DYS287 locus. This study has provided information on the pattern of DYS287 Y Alu Polymorphism in Kelantan-Malay, Jawa-Malay, Minangkabau-Malay, Banjar-Malay, Bugis-Malay and Rao-Malay sub-ethnic group in Peninsular Malaysia. Further study will be done on more samples of the other Malay sub-ethnic groups in Peninsular Malaysia to determine more DYS287 Y Alu Polymorphism status.